2011
DOI: 10.1074/jbc.c110.178343
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-d-glucosaminylphosphatidylinositol De-N-acetylase from Entamoeba histolytica

Abstract: PIG-L/GPI12 proteins are endoplasmic reticulum-resident membrane proteins involved in the second step of glycosylphosphatidylinositol anchor biosynthesis in eukaryotes. We show that the Entamoeba histolytica PIG-L protein is optimally active in the acidic pH range. The enzyme has an intrinsic low level of de-N-acetylase activity in the absence of metal and is significantly stimulated by divalent cations. Metal binding induces a large conformational change in the protein that appears to improve catalytic rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 21 publications
(30 reference statements)
5
35
0
Order By: Relevance
“…GPI-GnT assay was done using microsomes from each strain with 1000 g of total protein, as described previously (11).…”
Section: Preparation Of Microsomes From C Albicans and Gpi-gntmentioning
confidence: 99%
“…GPI-GnT assay was done using microsomes from each strain with 1000 g of total protein, as described previously (11).…”
Section: Preparation Of Microsomes From C Albicans and Gpi-gntmentioning
confidence: 99%
“…In a previous report we showed that unlike rat PIG-L and other known de-Nacetylases, EhPIG-L is actually capable of low activity in the absence of metal, and the catalysis is stimulated by divalent cations (9). We also showed that, unlike other known PIG-L enzymes, EhPIG-L preferred divalent cations such a Mg 2ϩ , Mn 2ϩ , or Co 2ϩ rather than Zn 2ϩ…”
mentioning
confidence: 79%
“…Briefly, protein expression was induced with 0.25 mM isopropyl 1-thio-␤-D-galactopyranoside, and the cells were grown at 16°C for another 16 h. The proteins were affinity-purified from amylose beads and used without removal of the MBP tag for all the enzyme assays. We have previously shown that the MBP tag does not significantly alter the activity of the enzyme (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations